Kirim Kali Ritual: The Interaction Between Tradition and Identity in Banaran Hamlet, Karanganyar - Natasya Sephiana Dewanti; Iis Lestari; Frida Dwi Handayani; Devi Nur Aini; Fitroh Naqiyah (Javanologi: International Journal of Javanese Studies, 2024)
The kirim kali ritual: The Interaction between Tradition and Community Identity in Banaran Hamlet, Karanganyar. The kirim kali ritual is a form of respect for the river as a source of life and fertility, which reflects the interaction between tradition and society. The ritual held annually in the month of Suro is an expression of gratitude for blessings and respect for ancestors and religious beliefs. This research aims to find out the interaction between tradition and identity of the Banaran Hamlet community as a result of the implementation of the kirim kali ritual. Through a qualitative approach with the type of field research, this study investigates how the culture and tradition of kirim kali affect the identity and social interaction in the community of Banaran Hamlet. The results showed that the implementation of the kirim kali ritual strengthens solidarity and emotional closeness among the community members of Banaran Hamlet. This shows that the kirim kali ritual not only celebrates cultural heritage, but also plays a role in building and strengthening identity as a community that values tradition and religion in the midst of social and global changes.